Invasion: Guyana's principled position on the invasion of the sovereign state of Grenada ([Government of Guyana] [Georgetown]GY)
Comprises a small collection of articles, statements and resolutions which all indicate Guyana's principled position on the United States-led invasion of sovereign CARICOM member-state Grenada in October 1983.
DC